The Structure and Form of the French Enlightenment, Volume 2 : Esprit Revolutionnaire - Wade, Ira Owen, 1896- (Princeton legacy library., 2015)
The author describes the influence on the Enlightenment of the intellectual currents that had been active in France, particularly the historical and humanistic esprit critique and the scientific esprit moderne. The second volume probes the writings of Morelly, Helvetius, Holbach, Mably, and Condorcet as they reveal the transformation of the esprit philosophique into the esprit revolutionnaire.